Civil liability and misuse of electronic communication means via websites: An analytical study in light of the law and policies of the United Arab Emirates - Yas, Nadia; Salem, Omnia; AlLouzi, Adel Salem; Abdalaziz, Maha Mustafa Omer; Marks, Adam; Al-Jumaili, Ahmed (Research Journal in Advanced Humanities, 2025)
advancements affecting social relations. Digital technology has had a significant impact on individuals' lives. The emergence of modern means of communication has had a substantial effect on social relations. The increase in these relations has led to new ties that did not exist before and have taken on contemporary forms. Social media has become one of the essential tools in the alternative press due to its multidimensional role, whether at the political, social, or cultural level. At the same time, it is considered one of the threats to countries and societies, as some resort to misusing it to spread rumors and malicious lies. Moreover, the misuse of social media is one of the significant negatives arising from it, as these platforms have become venues for spreading rumors, insults, slander, violations of privacy, and harmful practices facilitated by a lack of electronic controls governing their use. The modern era is witnessing a massive revolution in electronic communication. The use of these platforms has spread rapidly, and they have evolved in their methods, types, services provided, and applications. Their broad scope and ease of use have made them accessible to all individuals and societies, serving various activities, services, and purposes.